PENGARUH DOSIS PUPUK BOKASI KOTORAN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) LOKAL MUNA PADA LAHAN MARGINAL - NURCAYA, NURCAYA; KARIMUNA, LA; SUBAIR, IMRAN; SABARUDDIN, LAODE; RAHNI, NINI MILA; ARSYAD, MIRZA ARSIATY (Jurnal Agroteknos, 2022)
The aim of this research was to study the effect of cow manure bokashi fertilizer on the growth and yield of local Muna peanuts on marginal land. The research was conducted in the Experimental Garden Field II, Faculty of Agriculture, Halu Oleo University, Kendari, from April to June 2021. The study used a randomized block design (RBD) consisting of controls without applying bokashi fertilizer, 5 t ha-1 bokashi fertilizer, 10 t ha-1 bokashi fertilizer, bokashi fertilizer 15 t ha-1, bokashi fertilizer 20 t ha-1. Each treatment was repeated 3 times so that there were 15 experimental units. The variables observed were plant height, stem diameter, number of leaves, leaf area, number of pods, pod weight, seed weight, number of nodules and production. The results showed that the application of cow dung bokashi fertilizer doses on the growth and yield of muna local peanut plants on marginal land had a significant effect on the growth and yield variables of peanut plants. The best treatment was obtained at a dose of 20 t ha-1 bokashi fertilizer compared to other treatments and controls.